Efektivitas Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Berbantuan Alat Peraga dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Pembelajaran Matematika - Susilawati, Susi; Tio Heriyana (Indo-MathEdu Intellectuals Journal, 2024)
The study aims to test the effectiveness of a Numbered Head Together (NHT) cooperative learning model with a tool in improving students' ability to think critically about learning mathematics. The research method used is quantitative with the type of Quasi-experimental research. The study population was class X students of SMA Negeri 1 Cigugur in the 2023-2024 school year, with samples taken using purposive sampling technique, namely classes X1 and X2 with a total of 64 students and the statistical test used was t-test. The instruments used included testing students' critical thinking skills and elevating students' responses. Data analyzed using test instruments and analysis of mathematical critical thinking abilities. The results of the study showed that there was a difference in average mathematical critical thinking skills between students who obtained cooperative NHT-type learning with a tool compared to students who gained conventional learning. Normality tests and homogenity tests show that the N-Gain Score data are distributed normally and the data variance is homogeneous. The results of the hypothesis test showed a significant improvement in students' ability to think critically in the experimental group. Students' response to the NHT learning model was also positive